2022
DOI: 10.1002/ags3.12571
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor size in pathological T4 colorectal cancer with desmoplastic reaction and prognosis

Abstract: Background Tumor size in pathological T4 (pT4) colorectal cancer (CRC) is associated with oncological prognosis; however, its relation to epithelial‐mesenchymal transition (EMT)‐associated histology is unclear. We aimed to investigate the association of tumor size with oncological prognosis and EMT. Methods We performed a retrospective analysis of 95 patients with primary CRC who underwent radical surgery and were consecutively diagnosed with pT4. Results Both 3‐y disease‐free survival (DFS) and cancer‐specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This finding contrasted with other stages and highlighted the nuanced impact of tumor size on survival, depending on the stage of the disease. After a thorough literature search, we found that previous studies have revealed this seemingly paradoxical finding [ 23 , 32 37 ]. For example, Huang et al analysed 7719 patients with stage II colon cancer from the SEER database and indicated that patients with smaller tumors were associated with decreased CSS compared with those with larger tumors [ 32 ].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This finding contrasted with other stages and highlighted the nuanced impact of tumor size on survival, depending on the stage of the disease. After a thorough literature search, we found that previous studies have revealed this seemingly paradoxical finding [ 23 , 32 37 ]. For example, Huang et al analysed 7719 patients with stage II colon cancer from the SEER database and indicated that patients with smaller tumors were associated with decreased CSS compared with those with larger tumors [ 32 ].…”
Section: Discussionmentioning
confidence: 85%
“…Their study was limited by the small sample size. In addition, Shiraishi et al performed a retrospective study of 95 patients with pT4 CRC and demonstrated that tumor size ≥ 50 mm was associated with a better CSS than that of < 50 mm [ 23 ]. This contrasting view should be interpreted with caution because only 95 patients were included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation